Penguatan Sistem Karantina Nasional Berbasis Digital dan Traceability dalam Mendukung Ketahanan Pangan dan Daya Saing Ekspor Indonesia Menuju Indonesia Emas 2045 - Sarwo Sikam (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
The increasing demands of global trade, the risk of transboundary diseases, and the stringency of sanitary and phytosanitary (SPS) standards require a more integrated, transparent, and risk-based national quarantine system. The partial readiness of digital systems and traceability mechanisms has the potential to weaken Indonesia’s food security and export competitiveness toward the vision of Golden Indonesia 2045. This study aims to analyze the strategic role of the quarantine system in national development, identify institutional and technical root problems, and formulate the most concrete and feasible policy alternatives. The method used is policy analysis with a multi-criteria analysis (MCA) approach to compare several solution alternatives based on effectiveness, efficiency, technical aspects, and political feasibility. The results indicate that the digital transformation of the national quarantine system based on traceability and risk-based intelligence is the most superior policy option, as it can simultaneously address data fragmentation, improve service efficiency, and strengthen biosecurity surveillance. This study recommends the development of a Quarantine Super App, full implementation of e-certification, integration with the National Logistics Ecosystem and Customs, and the strengthening of an artificial intelligence-based risk profiling system. Gradual implementation accompanied by performance indicator-based evaluation is key to the success of the policy in enhancing national food security and export competitiveness.